Impact of Bank-specific and Macroeconomic Factors on Non-Performing Loans in the Banking Sector of Nepal - Subedi, Netra Prasad (Janapriya Journal of Interdisciplinary Studies, 2023)
Non-performing loans (NPLs) in the banking sector serve as a crucial indicator for assessing the performance of banks, as the effective management of credit risk stands as a pivotal challenge for lending institutions. The study aimed to determine the significant determinants of bank-specific factors including bank types and macroeconomic factors that determine the magnitude of NPLs in the context of Nepal. The study has included 11 years of strongly balanced panel data of 16 commercial banks consisting of seven domestic private banks, six joint venture banks, and three government-owned banks and macroeconomic data for the period of 2011/12 to 2021/22. The study applied the Pool OLS regression model including bank-dummy variables to assess the impact of the bank-specific factors and macroeconomic factors. The results revealed that the non-performing loan is higher in government-owned banks with a high level of variability compared to domestic private banks and joint venture banks. The study concluded that capital adequacy (CAR), operating efficiency (OCR) and remittance (Remit) have a significant negative impact on NPLs whereas, credit mobilization (CDR) has a significant positive impact on NPLs. It also revealed that the presence of joint venture and domestic private sector banks significantly decreased the size of non-performing loans compared to the presence of government-owned banks in the banking industry. Moreover, ROA, the rate of inflation, and lending interest rates have a positive but insignificant effect on NPLs. Similarly, the GDP growth rate has a negative but insignificant effect on NPLs.